Personality and fitness consequences of flight initiation distance and mating behavior in subdominant male reindeer (Rangifer tarandus) - Strong, Justin; Weladji, Robert; Holand, Oystein; Roed, Knut; Nieminen, Mauri (Wiley, 2017)
Animal personality has been studied extensively in recent years, yet multidimensionality in tendencies of risk-related behavior, and the role of such consistency from a mating tactics perspective, is yet to be investigated. We used a semi-domesticated herd of reindeer (Rangifer tarandus) to examine individual subdominant male propensity to risk mating attempts on guarded females, as well as flight initiation distance (FID), within the personality paradigm to elucidate potential fitness consequences of consistency from an adaptive perspective. Data were collected at the Kutuharju Reindeer Research Station in Kaamanen, Finland, where measures of personality were generated using field observation data based on the relative frequency of dominant male-subdominant male agonistic interactions over 4years and subdominant males' FID measured over 1year. Individual propensity for transient mating attempts was not significantly repeatable and did not significantly predict reproductive success or somatic cost during the mating season. Individuals varied consistently in FID, and although repeatable, FID was not related to reproductive success or somatic cost. Proximate state-dependent or social mechanisms may be driving decision-making with respect to mating effort, whereas consistent between-individual differences in FID may be maintained by mechanisms unrelated to life-history trade-offs involving productivity.
Keywords: Rangifer tarandus; poro; käyttäytyminen; lisääntymiskäyttäytyminen; reindeer